Natação e desenvolvimento motor em idade escolar - Marques, Bárbara Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Swimming is a sport well suited to any age group, it worked properly when the individual stimuli that provides assist in human development. But water stimulation, is not something that is so easily in physical education in Brazil. Development corresponds to changes that occur throughout life, but that depends on the stimuli provided. Several studies have shown positive effects of swimming in relation to the child. This study aimed to verify if children swimmers and physical education classes have better motor development than those who do not practice the sport. Collection was done with two groups of 10 students between 9 and 11 years. As a group consisting of non-swimmers, and another formed by those that complement the physical education class with the regular practice of swimming. To develop the study was administered a battery of the proposed motor adapted Rosa Neto (2002) in which each child performed tasks corresponding to their chronological age (CA) and were only able to perform the task at a later age, when it was obtained successful in completing the task as originally proposed. At the end of the application of all statistical tests was done getting mean and standard deviation of the old motor (IM), calculated the ratio General Motor (MGQ) for the classification of the child's motor development and application of the t test with p <0.05 to observe the level of significance in the results. The results showed that the group swimmers had better agility tests which resulted in a difference between (IC) and (IM) higher compared with the non-practitioner. They also had higher average (MGQ), but these were not sufficient to classify the group into another level of development, however, by observing isolated cases, two children that practice would be a greater level of development. Through the t test was observed that the group swimmers had significant difference in balance ability. We conclude that the swimming group got positive overall...

A natação é um esporte muito indicado a qualquer faixa etária, pois quando trabalhada adequadamente proporciona ao indivíduo estímulos que auxiliam no desenvolvimento humano. Porém a estimulação aquática, não é algo que se encontra com tanta facilidade na educação física escolar do Brasil. Desenvolvimento corresponde a mudanças que ocorrem no decorrer da vida, mas que dependem dos estímulos fornecidos. Diversos estudos mostraram efeitos positivos da prática da natação em relação ao desenvolvimento da criança. Este estudo teve por objetivo verificar se as crianças praticantes de natação e de aulas de educação física têm melhor desenvolvimento motor do que aquelas que não praticam a modalidade. Foi feito coleta com dois grupos de 10 escolares entre 9 e 11 anos. Sendo um grupo constituído por não praticantes de natação, e outro formado por aqueles que complementam a aula de educação física com a prática regular da natação. Para o desenvolvimento do estudo foi aplicado uma bateria motora adaptada da proposta de Rosa Neto (2002) em que cada criança realizou tarefas correspondentes a sua idade cronológica (IC) e só puderam realizar a tarefa proposta para uma idade mais avançada, quando a mesma obtinha êxito na execução da tarefa proposta inicialmente. Ao final da aplicação de todos os testes foi feito análise estatística obtendo média e desvio padrão da idade motora (IM), calculado o quociente motor geral (QMG) para obter a classificação do desenvolvimento motor da criança e aplicação do teste t com p<0,05 para observar o nível de significância nos resultados. Os resultados mostraram que o grupo praticante de natação teve melhor desenvoltura nos testes o que acarretou uma diferença entre (IC) e (IM) maior comparada ao grupo não praticante. Também apresentaram maiores médias de (QMG), porém essas não foram suficientes para classificar o grupo em outro nível de desenvolvimento maior
Keywords: Natação; Capacidade motora; Educação fisica; Alunos; Ensino fundamental; Educação física - Estudo e ensino; Exercícios físicos; Swimming